Maximally restrictive leptonic texture zeros in two-Higgs-doublet models - Gonzalez Felipe, Ricardo (2017)
The implementation of maximally restrictive texture zeros in the leptonic sector is investigated in the context of two-Higgs-doublet models with Majorana neutrinos. After analyzing all maximally restrictive pairs of leptonic mass matrices with zero entries, we conclude that there are only four texture combinations that are compatible with observations at 3σ confidence level and can be implemented through Abelian symmetries in a two-Higgs-doublet model. The compatibility of these textures with current constraints on leptonflavor-violating processes is also studied. The ultraviolet completion of these models is discussed in the framework of the seesaw mechanism for neutrino masses.